'It struck at the heart of who I thought I was': A meta‐synthesis of the qualitative literature examining the experiences of people with multiple sclerosis. (24th June 2020) - Desborough, Jane; Brunoro, Crystal; Parkinson, Anne; Chisholm, Katrina; Elisha, Mark; Drew, Janet; Fanning, Vanessa; Lueck, Christian; Bruestle, Anne; Cook, Matthew; Suominen, Hanna; Tricoli, Antonio; et al.
Abstract: Background: People with multiple sclerosis (MS) have varied experiences and approaches to self‐management. This review aimed to explore the experiences of people with MS, and consider the implications of these experiences for clinical practice and research. Methods: A meta‐synthesis of the qualitative literature examining experiences of people with MS was conducted using systematic searches of ProQuest, PubMed, CINAHL and PsycINFO. We incorporated feedback from team members with MS as expert patient knowledge‐users to capture the complex subjectivities of persons with lived experience responding to research on lived experience of the same disease. Results: Of 1680 unique articles, 77 met the inclusion criteria. We identified five experiential themes: (a) the quest for knowledge, expertise and understanding, (b) uncertain trajectories (c) loss of valued roles and activities, and the threat of a changing identity, (d) managing fatigue and its impacts on life and relationships, and (f) adapting to life with MS. These themes were distributed across three domains related to disease (symptoms; diagnosis; progression and relapse) and two contexts (the health‐care sector; and work, social and family life). Conclusion: The majority of people in the studies included in this review expressed a determination to adapt to MS, indicating a strong motivation for people with MS and clinicians to collaborate in the quest for knowledge. Clinicians caring for people with MS need to consider the experiential and social outcomes of this disease such as fatigue and the preservation of valued social roles, and incorporate this into case management and clinical planning.